2016
DOI: 10.4103/0971-3026.195773
|View full text |Cite
|
Sign up to set email alerts
|

Solid renal masses in adults

Abstract: With the ever increasing trend of using cross-section imaging in today's era, incidental detection of small solid renal masses has dramatically multiplied. Coincidentally, the number of asymptomatic benign lesions being detected has also increased. The role of radiologists is not only to identify these lesions, but also go a one step further and accurately characterize various renal masses. Earlier detection of small renal cell carcinomas means identifying at the initial stage which has an impact on prognosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The initial evaluation of parenchymal kidney lesions is usually done using B-mode US, which mainly distinguishes between cystic lesions and solid renal masses. For RCCs, gray scale US imaging shows an isoechoic or mildly hyperechoic, homogeneous or, especially for larger tumors, heterogeneous, solid parenchymal renal mass, with or without capsular bulging [ 37 ]. The additional use of color Doppler US allows for intra-tumor vascular distribution assessment and for additional quantification of RCC large vessel invasion, i.e., the detection of the characteristic RCC tumor thrombus extension, into the renal veins and/or inferior vena cava.…”
Section: The Role Of Current Imaging Modalities In Rcc Clinical Work-upmentioning
confidence: 99%
“…The initial evaluation of parenchymal kidney lesions is usually done using B-mode US, which mainly distinguishes between cystic lesions and solid renal masses. For RCCs, gray scale US imaging shows an isoechoic or mildly hyperechoic, homogeneous or, especially for larger tumors, heterogeneous, solid parenchymal renal mass, with or without capsular bulging [ 37 ]. The additional use of color Doppler US allows for intra-tumor vascular distribution assessment and for additional quantification of RCC large vessel invasion, i.e., the detection of the characteristic RCC tumor thrombus extension, into the renal veins and/or inferior vena cava.…”
Section: The Role Of Current Imaging Modalities In Rcc Clinical Work-upmentioning
confidence: 99%
“…13 The role of DWI MRI as a biomarker for the investigation of benign or malignant renal masses, subtypes of RCC, and histological grades is under evaluation. 7 There are several strengths and limitations to the use of MRI. MRI can be effective in the characterization of renal lesions when DMS and CT imaging methods are not sufficient.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…2,3 Ultrasound (US)-and Computed tomography (CT)-guided percutaneous renal tumour biopsy (PRTB) is a common procedure following an incidental finding of an indeterminate renal mass on either a magnetic resonance (MR) or CT scan. 4 Studies have shown that PRTB prior to treatment is of high diagnostic value and a favourable option regarding subtype histopathological analysis of the presented renal mass in regard to accuracy and rate of complications. 5 Percutaneous renal tumour biopsy has been proven to be of use in an outpatient setting with a short post-biopsy observation time, when sudden onset complications are not present, proving it to be an efficient and reliable choice.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Ultrasound (US)- and Computed tomography (CT)-guided percutaneous renal tumour biopsy (PRTB) is a common procedure following an incidental finding of an indeterminate renal mass on either a magnetic resonance (MR) or CT scan. 4 Studies have shown that PRTB prior to treatment is of high diagnostic value and a favourable option regarding subtype histopathological analysis of the presented renal mass in regard to accuracy and rate of complications. 5 …”
Section: Introductionmentioning
confidence: 99%